Effect of the www.dailyesl.com website as a technological and pedagogical resource fot teaching english at El Flor Elementary School, 2015 - Caballero Guerra, Stephanie (UDELAS, 2015)
Panamá is recognzed internationally as a center of business trade, and the best country of mCentral America for tourism. Regarding these aspects, it can be said that most of the negotiations are handle in English language and that ost of the tourist that come also use English as the lingua franca.